Performance of physical shell foundation model under axial loading - Ab Rahman, Amera Ratia (2016)
The development of shell theory has added new and exciting dimension to modem Civil Engineering, particularly in the design of super structures. Shells foundations, by virtue of its fo1m will necessarily be more economical. This research is primarily focused on the behavior of three different shapes of foundation viz; pyramidal shell foundation, hyperbolic paraboloid shell foundation and square flat foundation under axial loading with different founding levels. Three different height/ thickness ratio of flat and shell foundation made out of different materials (namely Plaster of Paris and polyester resin) were studied. All foundations were subjected to loading test in a soil box as purposefully designed and fabricated special for this research to model testing conditions. The test observation of foundation model was measured using dial gauges to observe the stress characteristic deformation. Experimental results from direct shear test, particle size distribution, specific gravity and compression test were analyzed to characterize the material tested (sand and sponge). Results from foundation loading tests presented in graphical form show that that foundation shape, shell aspect ratio and embedment depth significantly affected the result of load carrying capacity. The load carrying capacity of shell footing was found to increase with shell aspect ratio (0.3, 0.4 and 0.5) and embedment depth increase from 0.3 to 0.5 compared to the square flat foundation for a similar cross-sectional area. Crack patterns were observed to investigate the movement and the location of crack. The crack pattern for shell foundation started initially in the corner of edge beams. However, for the square flat foundation, failure mechanism was distributed over the whole foundation starting at the edge of foundation and ended at column base interface. Shell foundation showed higher load bearing values compared to square flat foundation